The Effect of Oral Administration of Fermented Rice by Monascus purpureus JmbA on Blood of Hypercholesterolemia White Mouse (Rattus sp.) - EVI TRIANA; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
Fermented rice by Monascus purpureus, namely angkak, produces lovastatin. Lovastatin is believed and studied as anti-hypercholesterolemic agent. Somehow, its effects on blood parameters were less known. Therefore, a study on the effect of angkak on erythrocyte, leukocyte, thrombocyte, and haemoglobin level was conducted, involving 15 male Sprague Dawley strain white mice that were divided into 5 treatment groups. The result showed that oral administration of angkak beared lovastatin to the hipercholesterolemic mice could increase the number of trombocyte during the study. Increasing the number of thrombocyte was different depended on dosage of angkak. The optimum dosage was 0.1 g/day. Angkak could also increase haemoglobin concentration and the number of leucocyte, although that raise did not depend on dosage of angkak. Meanwhile, the number of erythrocyte was not affected by angkak.Key words: angkak, erythrocyte, hemoglobin, leukocyte, lovastatin, thrombocyte